Ferroptosis-associated microRNAs: Systematic review: Ferroptosis-associated microRNAs - Candia Plata, Maria del Carmen; Martínez Soto, Juan Manuel; Arredondo Damián , Jeanette Guadalupe; Ramírez Romero, Astrid Nallely Ramírez Romero; Villegas Coronado, Lucía Guadalupe; Soto Guzmán , Jesús Adriana; López Soto, Luis Fernando; Mata Pineda, Ana Lourdes; Álvarez Hernández , Gerardo; Galván Moroyoqui, José Manuel (Cellular and Molecular Biology, 2025)
Ferroptosis, an iron-dependent form of regulated cell death characterized by lipid peroxidation, has emerged as a critical process in various diseases. MicroRNAs (miRNAs), small non-coding RNAs that regulate gene expression, are increasingly recognized as key modulators of ferroptosis pathways. This systematic review aims to provide a comprehensive overview of the current knowledge regarding miRNAs implicated in ferroptosis across a spectrum of diseases. We conducted a systematic search of EMBL-EBI, PubMed, Scopus, and Web of Science databases to identify relevant studies published up to October 31, 2022. Our search strategy identified 127 articles encompassing 107 distinct miRNAs that influence ferroptosis. This review synthesizes the findings of these studies, highlighting the specific miRNAs that act as either inhibitors or inducers of ferroptosis in different disease contexts, including various cancers (e.g., lung, breast, colorectal) and degenerative conditions (e.g., acute renal failure, diabetic retinopathy). We discuss the molecular mechanisms by which these miRNAs regulate ferroptosis, often by targeting key genes involved in iron metabolism, lipid peroxidation, and antioxidant defense. Furthermore, we explore the potential of these miRNAs to serve as diagnostic biomarkers and therapeutic targets in ferroptosis-related disorders, offering insights into novel strategies for disease management.